Expansão, democratização e eficiência de universidades federais do nordeste em perspectiva comparada - Lopes, Débora de Oliveira (2023)
The present study has as its theme the expansion, democratization and efficiency of Federal Universities in the northeast region. The general objective of the present investigation is to comparatively analyze the largest Federal Institutions of Higher Education (IFES) in the region and understand how their performance was given in the face of public policies of expansion and democratization to which they were submitted since 2007. The IFES have faced measures that have hindered their expansion, their full functioning and their autonomy, thus highlighting the importance of fully taking advantage of the period favorable to the expansion and democratization of the IFES experienced in 2007 and subsequent years. It is questioned, therefore, whether the IFES in the Northeast were considered efficient during this period. In this sense, through a literature review and documentary research, expansion, democratization and efficiency were discussed, highlighting the evaluation policies of the IFES. And based on data obtained from the Managerial Treasury, CAPES, MEC and Management Reports of the universities made available by TCU, the analysis of this research was carried out. For this purpose, Data Envelopment Analysis – DEA was used, under the CCR model that deals with constant returns to scale, using management indicators established by the Federal Court of Auditors as inputs and outputs. The results obtained from the efficiency frontier determined that of the nine universities studied, only two were considered efficient during the entire analyzed period. The DEA model proposed goals and targets necessary for the inefficient IFES to reach the production frontier based on the results presented by the efficient IFES, considered here as benchmarks.